Understanding Participatory Governance: An Analysis of Participants' Motives for Participation. (July 2017) - Gustafson, Per; Hertting, Nils
Despite the growing body of literature on participatory and collaborative governance, little is known about citizens' motives for participation in such new governance arrangements. The present article argues that knowledge about these motives is essential for understanding the quality and nature of participatory governance and its potential contribution to the overall political and administrative system. Survey data were used to explore participants' motives for participating in a large-scale urban renewal program in Stockholm, Sweden. The program was neighborhood-based, characterized by self-selected and repeated participation, and designed to influence local decisions on the use of public resources. Three types of motives were identified among the participants: (a) Common good motives concerned improving the neighborhood in general and contributing knowledge and competence. (b) Self-interest motives reflected a desire to improve one's own political efficacy and to promote the interest of one's own group or family. (c) Professional competence motives represented a largely apolitical type of motive, often based on a professional role. Different motives were expressed by different categories of participants and were also associated with different perceptions concerning program outcomes. Further analysis suggested that participatory governance may represent both an opportunity for marginalized groups to empower themselves and an opportunity for more privileged groups to act as local "citizen representatives" and articulate the interests of their neighborhoods. These findings call for a more complex understanding of the role and potential benefits of participatory governance.